In-situ surface roughness measurement for mass finishing - Kor, Wei Sheng (Nanyang Technological University, 2020)
Surface roughness is an important characteristic to determine how an object interact with the environment around it. Mechanical stylus measurement has always been a popular and conventional measurement method for measuring surface roughness. The aim of this project was to create a surface roughness measurement system to measure surface roughness of samples on site after mass finishing. By using chromatic confocal method to achieve non-contact surface roughness measurement, the aim was to substitute the current mechanical stylus method being used. The chromatic confocal sensor was integrated with the motorised linear stage to form a surface roughness measurement system. The focus of the project is to develop the data acquisition software for the chromatic confocal sensor and motion control for the motorised linear stage to achieve in-situ measurement of surface profile. To determine the inspection system designed effectiveness and feasibility, it was evaluated based on its accuracy when compared with the current stylus profilometer method that is being utilised. Experiments shows that the inspection system designed is not capable of substituting the stylus profilometer due to the vibration from the motorised stage. However, if the vibration issue is rectified, it has the potential for in-situ measurement capability.